The Poet Abu Bakr Ahmad Al-Satali (D. 676 AH): His poetic Purposes and the Tributaries of his Image - An Artistic Study - Hassan, Nibras Hamad; Ahmed, Firas Abdel Rahman (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to understand the artistic dimensions in the poetic themes of Abu Bakr Ahmad Al-Sittali and to shed light on the sources of imagery that rely on the poet’s intellectual background from which he derived his images. Methods: The study relied on the artistic method in observing and analyzing the poetic texts derived from Al-Sittali’s poetry to identify elements of beauty and creativity according to the research requirements. Results: Al-Satali’s poetry contains a vast amount of sincerity in most of the subjects he depicted, particularly those related to his feelings of alienation due to his move from his birthplace to another location. It was also found that the presence of nature in his poetry alternates between love, calmness, tranquility, and awe and strength, demonstrating his artistic ability in crafting his poetic imagery. Conclusion: His poetry stems from the pulse of his feeling in portraying his reality. Al-Satali did not differ from previous poets in his use of imagery in his poetic themes; what distinguished him was his unique way of forming his expressions, which stimulated the reader’s imagination. He relied on important elements for his poetic imagery, including the Quran, poetic and historical heritage, and the images of nature with all its elements, which he found to be a vast outlet for expressing his emotions and reflections.